The Neurophysiological Validation of the Hyperpolarization Theory of Internal Inhibition - Shulgina, Galina I. (The Spanish Journal of Psychology, 2005)
The experiments in conscious non-immobilized rabbits showed that cessation of the reactions without reinforcement (elaboration of the internal inhibition) is accompanied by an enhanced phasic state, by alternation of activation and inhibition of neuron firing, and by the corresponding slow potential oscillation (SPO). These changes can be either localized, predominantly in the structures of conditioned stimulus, or, under enhancement of the inhibitory state, generalized in the brain structures. On the basis of our experience and published data, it is concluded that the above event results from relative enhancement of the inhibitory hyperpolarizing processes due to increase in reactivity of the inhibitory systems to stimulus, which acquires inhibitory properties during learning. Changes in the excitability and reactivity of neuron populations appearing during enhancement of the hyperpolarizing inhibition, and differing in the various brain structures, play an active role in the execution of the main function of the internal inhibition: limitation of excitation transmission to the effectors. An inhibitory mediator gamma aminobutyric acid (GABA) is of great importance in inhibiting the excitation in response to the stimulus which lost its biological significance. These experimental data and their interpretation in the light of published data give the basis for the development of the hyperpolarization theory of internal inhibition.